2010
DOI: 10.1029/2010ja015277
|View full text |Cite
|
Sign up to set email alerts
|

Electric field statistics and modulation characteristics of bursty Langmuir waves observed in the cusp

Abstract: [1] HF wave receivers on the Twin Rockets to Investigate Cusp Electrodynamics (TRICE) detect numerous 20-250 ms duration Langmuir wave bursts. Investigation of 41 bursts at 967-984 km, where the gyrofrequency exceeds the plasma frequency, reveals a characteristic signature whereby the Langmuir wave bandwidth and highest frequency maximize at the center of the bursts, suggesting that bursts coincide with density enhancements. The Langmuir waveforms are modulated at frequencies up to 50 kHz, with significant mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…32 All three experiments show that Langmuir waves in the polar cusp ionosphere have waveform modulations of order 100%, with modulation frequencies ⌬f ranging from less than 1 kHz up to 50 kHz. Qualitatively, the modulated Langmuir waveforms observed in all three experiments closely resemble those in Figs.…”
Section: Applications To Trice Datamentioning
confidence: 98%
See 3 more Smart Citations
“…32 All three experiments show that Langmuir waves in the polar cusp ionosphere have waveform modulations of order 100%, with modulation frequencies ⌬f ranging from less than 1 kHz up to 50 kHz. Qualitatively, the modulated Langmuir waveforms observed in all three experiments closely resemble those in Figs.…”
Section: Applications To Trice Datamentioning
confidence: 98%
“…The multiply peaked spectra, together with the consistency of the simulated and observed waveforms, suggest an interpretation of the Langmuir waveform data in terms of multiple independently growing, relatively narrow bandwidth waves. 32 Furthermore, applying Eq. ͑10͒ to the observations of the upper limit ⌬f Ϸ 50 kHz implies that t c տ 2͑⌬͒ −1 = ͑⌬f͒ −1 Ϸ͑50 kHz͒ −1 =20 s for the Langmuir waves.…”
Section: Applications To Trice Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing STEREO/WAVES measurements with theoretical models, they concluded that scattering of Langmuir waves by density fluctuations is mandatory to reproduce such a behavior. Finally, LaBelle et al (2010) also invoke the linear growth of Langmuir waves in an homogeneous medium to explain the highly modulated electric waveforms observed in the Earth polar cusp.…”
Section: Role Of Density Fluctuations In the Dynamics Of Langmuir Wavesmentioning
confidence: 98%